Synthesis, in vitro and in silico evaluation of novel trans-stilbene analogues as potential COX-2 inhibitors. Issue 1 (1st January 2018) - Regulski, Miłosz; Piotrowska-Kempisty, Hanna; Prukała, Wiesław; Dutkiewicz, Zbigniew; Regulska, Katarzyna; Stanisz, Beata; Murias, Marek
Graphical abstract: Abstract: 25 new trans -stilbene and trans -stilbazole derivatives were investigated using in vitro and in silico techniques. The selectivity and potency of the compounds were assessed using commercial ELISA test. The obtained results were incorporated into 2D QSAR assay. The most promising compound 4-nitro-3′, 4′, 5′-trihydroxy- trans -stilbene (N1) was synthetized and its potency and selectivity were confirmed. N1 was classified as preferential COX-2 inhibitor. Its ability to inhibit COX-2 in MCF-7 cell line was established and its cytotoxicity by MTT test was assessed. The compound was more cytotoxic than celecoxib within studied concentration range. Finally, the investigated trans -stilbene was docked into COX-1 and COX-2 active sites using "CDOCKER" protocol.